Morphological and molecular characterization of a hybrid zone between Prosopis alba and P. nigra in the Chaco region of northwestern Argentina - Vega, Carmen Delcira; Teich, Ingrid; Acosta, Maria Cristina; Lopez Lauenstein, Diego; Verga, Anibal; Cosacov, Andrea (JD Sauerlaender's Verlag, 2021)
The Gran Chaco is the largest dry forest in South America. One of the key taxa of this biome is the genus Prosopis (Fabaceae) which contains several economically important species. One of the characteristics of this genus is its natural capacity to exchange genetic information among congeneric species, generating zones of high morphological and genetic variability at contact points. The study and management of these contact areas can contribute to the dynamic conservation of these native genetic resources. In this study, we analysed three sites within a gradient of land aridity, where P. nigra and P. alba grow in sympatry and apparently hybridize. This is the first study performed in both, Prosopis pure sites and hybrid swarm, which includes a spatially explicit approach and simultaneously analyses fruit and leaf morphological variation, together with molecular information (microsatellites markers). We performed a multivariate morphological analysis, Bayesian genetic clustering and multivariate associations between genetic and morphological variability in the pure parental populations and in the hybrid swarm, considering possible spatial autocorrelation. Bayesian cluster analysis revealed two distinct groups corresponding to each species, differentiating the pure morphotypes from sites 1 and 2. Site 3, corresponding to the hybrid swarm, was composed of pure P. alba and P. nigra trees and hybrid individuals. We found morphological and molecular evidence of hybridization between P. alba and P. nigra, and detected novel phenotypes in the hybrid site.